Accounting Students' Feedback on Feedback in Australian Universities: They're Less Than Impressed - Watty, K.; De Lange, Paul; Carr, R.; O'connel, B.; Howieson, B.; Jacobsen, B. (Routledge, 2013)
Undergraduate accounting students in Australian universities are dissatisfied with the feedback that they currently receive. Recent evidence from the Course Experience Questionnaire (CEQ, a national survey of Australian university graduates) suggests that the accounting discipline ranks poorly on assessment feedback when compared to other disciplines. This finding aligns with the results of local university data, which also shows that students appear dissatisfied with feedback. Similar results can be found in other jurisdictions, as noted by the Higher Education Academy in the UK. Given the importance of feedback to enhancing students’ learning, these results are of concern to accounting academics and other stakeholders, including professional accounting bodies and graduate employers. To date, few studies have sought to understand in a comprehensive manner the relatively poor performance in feedback scores in the discipline of accounting. This exploratory study seeks to address this gap by investigating the reasons underlying students’ dissatisfaction. We report on students’ perceptions obtained from a large survey of Australian undergraduate accounting students across 12 universities. Over 2600students responded to the survey. Our findings indicate that accounting students value feedback that is individualised, detailed, constructive and timely, and that currently they are not receiving feedback with these attributes.